2012
DOI: 10.1186/ar4107
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 is elevated in synovial fluid of patients with focal cartilage defects and stimulates cartilage matrix production in an in vitro regeneration model

Abstract: IntroductionThis study aimed to determine whether, as in osteoarthritis, increased levels of interleukin-6 (IL-6) are present in the synovial fluid of patients with symptomatic cartilage defects and whether this IL-6 affects cartilage regeneration as well as the cartilage in the degenerated knee.MethodsIL-6 concentrations were determined by ELISA in synovial fluid and in conditioned media of chondrocytes regenerating cartilage. Chondrocytes were obtained from donors with symptomatic cartilage defects, healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 75 publications
5
79
0
2
Order By: Relevance
“…Patients undergoing primary shoulder arthroplasty were not used as controls because of inconsistency in the literature regarding alterations in synovial fluid biomarkers in osteoarthritis. 24,33 During surgery for this control group, intraoperative synovial fluid was obtained through an arthroscopic portal at the start of the procedure and sent for a-defensin analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Patients undergoing primary shoulder arthroplasty were not used as controls because of inconsistency in the literature regarding alterations in synovial fluid biomarkers in osteoarthritis. 24,33 During surgery for this control group, intraoperative synovial fluid was obtained through an arthroscopic portal at the start of the procedure and sent for a-defensin analysis.…”
Section: Methodsmentioning
confidence: 99%
“…High IL-6 levels are observed in the serum and synovial tissue of patients with RA (Tsuchida et al, 2012). It has been observed that polymorphisms in the IL6 gene promoter region may be responsible for changes in the expression of IL-6 (Spoto et al, 2015), leading to an increase in the inflammatory process and the development of radiographic joint damage in hands.…”
Section: Discussionmentioning
confidence: 98%
“…IL-6 activity in synovial fluid in OA patients has been reported [18,120]. Elevated concentrations of IL-6 have been found in OA patients [113]. MMPs promote breakdown of cartilage and are involved in the progression of OA as MMPs are responsible for degradation process in OA cartilage [120].…”
Section: Analysis Of Cytokines and Wear Particles In Oa Processmentioning
confidence: 98%
“…Cytokines may play an important role in OA [113]. Some cytokines can inhibit production of the cartilage matrix and therefore influence the balance between synthesis and degradation of the tissue matrix [18].…”
Section: Analysis Of Cytokines and Wear Particles In Oa Processmentioning
confidence: 99%